A Narrative Inquiry Approach to the Design and Practice of Early English Education in Chinese Families - Yue, Zhang; Hanif , Mohd Hafiz (International Journal of Education and Humanities, 2025)
This study employed a narrative inquiry method. It used qualitative techniques such as in-depth interviews, family diaries, video recordings, and field observations. The study systematically examined the design and practice of early English education in Chinese families. Globalization has accelerated. The importance of English as an international language continues to rise. Families serve as key environments for early language learning. Their educational settings, parental teaching strategies, and emotional support significantly influence children’s learning motivation and oral expression. The study developed a theoretical model: Family Factors → Interest Stimulation → Motivation Formation → Enhanced Oral Expression. Analysis of several representative family cases revealed key factors. A warm and open family environment played a crucial role. Diversified teaching methods—such as parent-child reading, picture book reading, nursery rhyme instruction, scenario simulation, and interactive games—were important. A positive shift in parental attitudes and effective resource integration also contributed significantly to stimulating children’s learning motivation. Parents continuously adjusted their teaching strategies. They enriched language input and created authentic communication scenarios. These efforts significantly improved children’s English oral expression skills. This study provides empirical support for early English education theories. It offers valuable guidance for parents, teachers, and policymakers in developing scientific and systematic family English education strategies. The findings promote a shift from traditional exam-oriented models to approaches that emphasize emotional experience and communicative practice